Taeniasis Solium dan Sistiserkosis pada Manusia - Elva Susanty (Fakultas Kedokteran Universitas Riau, 2018)
Taenia solium taeniasis (taeniasis) and cysticercosis in human are infectious diseases caused by pork tapeworm Taenia solium. They are zoonotic diseases and still a health problem in the world, especially in developing countries such as Indonesia. The prevalence of taeniasis and cysticercosis in Indonesia is still quite high at 2% - 48% with the highest prevalence in Papua. Human taeniasis can manifest as a asymptomatic or intestinal minimally symptomatic. Cysticercosis can involve of neural tissue (neurocysticercosis) may manifest epilepsy seizure, headache, neurological symptom, cognitive disabilities, and death. The habit of eating raw or undercooked pork, lack of sanitation, and a lack of supervision the slaughterhouse are some of the factors causing taeniasis and cysticercosis in human. Avoiding eating raw pork, cooking meat over temperature 54oC, supervision at slaughterhouses, and maintaining hygiene is a way to prevent taeniasis and cysticercosis, therefore it is necesarry to do more intensive programs to prevent and control the diseases.